Diglossia and language contact : language variation and change in North Africa - Sayahi, Lotfi (Cambridge : Cambridge University Press, 2014)
This volume provides a detailed analysis of language contact in North Africa and explores the historical presence of the languages used in the region, including the different varieties of Arabic and Berber as well as European languages. Using a wide range of data sets, it provides a comprehensive analysis of the mechanisms of language contact under classical diglossia and societal bilingualism, examining multiple cases of oral and written code-switching. It also describes contact-induced lexical and structural change in such situations and discusses the possible appearance of new varieties within the context of diglossia. Examples from past diglossic situations are examined, including the situation in Muslim Spain and the Maltese Islands. An analysis of the current situation of Arabic vernaculars, not only in the Maghreb but also in other Arabic-speaking areas, is also presented. This book will appeal to anyone interested in language contact, the Arabic language, and North Africa.
1. Introduction -- 2. The languages of the Maghreb -- 3. Diglossia and bilingualism in the Maghreb -- 4. Language contact under diglossia and bilingualism -- 5. Lexical borrowing under diglossia and bilingualism -- 6. Diglossia and contact-induced language change -- 7. Diglossia and the emergence of new varieties -- 8. Conclusion.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Languages in contact -- Africa, North; Diglossia (Linguistics); Africa, North -- Languages